2005
DOI: 10.1097/01.prs.0000177687.83247.27
|View full text |Cite
|
Sign up to set email alerts
|

Two Hundred Ninety-Four Consecutive Facial Fractures in an Urban Trauma Center: Lessons Learned

Abstract: The experience at a high-volume level I trauma center with residents as the primary physicians has confirmed that facial trauma surgery may be undertaken with an acceptably low complication rate. Numerous technical factors were thought to be responsible for this, including the use of miniplates for treatment in the majority of mandibular fractures, overcorrection of orbital volume in fractures involving the globe, and the use of a transconjunctival incision with a lateral canthotomy for access to the lower eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 22 publications
6
64
1
3
Order By: Relevance
“…However, in the present study, mandible fractures were the most prevalent in most of the categories, and such result is in agreement with the literature [12][13][14][15][16]31,37 . Patients with nasal fractures can have associated injuries with varied degrees of complexity and severity.…”
Section: Discussionsupporting
confidence: 83%
“…However, in the present study, mandible fractures were the most prevalent in most of the categories, and such result is in agreement with the literature [12][13][14][15][16]31,37 . Patients with nasal fractures can have associated injuries with varied degrees of complexity and severity.…”
Section: Discussionsupporting
confidence: 83%
“…[10] Reports in which assaults were found to be the most common cause, with a rate of 48% of the cases, have also been published. [13] The rates of assaults, sport accidents, labor accidents, and falls in our study were compatible with those in the literature. [11] While only soft tissue injuries were present in 68% of the patients with head-and-neck injuries, there were accompanying bone fractures in 961 patients (32%).…”
Section: Discussionsupporting
confidence: 82%
“…[10][11][12][13] The rates of fractures elsewhere in the face in our study were compatible with those in the literature. [10][11][12] In our cases, the most frequent fractures were those of the symphysis-parasymphysis, with a rate of 44.3%, while they were reported to be seen at a rate of 29.3% in the literature as the second most common fractures.…”
Section: Discussionsupporting
confidence: 81%
“…Kelley et al reported that they account for about 5% of all facial fractures and we have also found this in our experience. 2 For many years, a large number of fractures of the naso-orbitoethmoid complex were sustained in road traffic accidents, but as cars have become safer they now occur less often. 3 Nowadays, most facial fractures are caused by interpersonal violence and sports accidents, 4,5 and these impacts differ considerably in velocity and power from those sustained in road crashes.…”
Section: Introductionmentioning
confidence: 99%